(untitled) (Bangladesh Journal of Medical Physics, 2013)
Radiation absorbed dose estimation was performed on eleven normal patients who were in a process of routine diagnostic investigation of the renal function. Bio-kinetics and bio-distribution of 99mTc-DTPA in patients was evaluated by dual-head gamma camera imaging and blood-plasma sample counting method. Radiation dose estimations were performed using standard MIRD techniques and biodistribution of different organ was estimated by drawing region of interest (ROI) according to MIRD phantom model [1]. From the time-activity curves, cumulative activities and residence times of 99mTc- DTPA in the kidneys, brain, upper large intestine (ULI), small intestine (SI), lower large intestine (LLI), stomach, heart, liver, lung and remainder of the body was calculated. Using the information of residence times of the total body and urinary bladder voiding at 2.4 hours on MIRD 12 absorbed dose for the 99mTc-DTPA in different target organs of the body was measured [2]. The estimated average absorbed dose to the kidneys as a target organ in normal Bangladeshis are 5.71E-03 mGy/MBq of 99mTc-DTPA which is closer to the ICRP 53 and other recent published data. The calculated effective dose equivalent and effective dose was found 5.72E-03 mSv/MBq and 4.89E-03 mSv/MBq respectively. DOI: http://dx.doi.org/10.3329/bjmp.v4i1.14674 Bangladesh Journal of Medical Physics Vol.4 No.1 2011 21-26